Optical Characterization of Porous Sputtered Silver Thin Films - Olivier Carton; Jaouad Ghaymouni; Michaël Lejeune; Andreas Zeinert (Journal of Spectroscopy)
The optical properties of various porous silver films, grown with a commercial DC sputter coater, were investigated and compared for different plasma parameters. Effective Drude models were successfully used for those films whose spectra did not show particular resonance peaks. For the other films, neither an effective Drude model nor effective medium models (Maxwell Garnett, Bruggeman, and Looyenga) can describe the optical properties. It turns out that a more general approach like the Bergman representation describes the optical data of these films accurately adopting porosity values consistent with physical measurements.